Exploring Trishanku Psyche in Nepali British Diaspora Poetry - Niroula, Dhundi Raj (Pursuits: A Journal of English Studies, 2024)
This present paper is an analysis of trishanku psyche in the poetry from the Nepalese British diaspora. It scrutinizes how Nepalese poetry composed at British diaspora celebrates the theme of repulsion and fascination of diaspora people towards their land of origin and land of relocation. Seven different poems written by seven different Nepalese poets living at British diaspora are examined in this paper. For the theoretical underpinnings, insights are borrowed from diaspora theorists, researchers and scholars such as W. Andy Knight, Israel Milton, Makrand Paranjape, William Saffron, Uma Parameshwaran, Nina Glick Schiller, Jani Hiral and Pabitra Bharali. Nepalese diasporic poets from around the world including British diaspora express cultural dilemma, divided loyalty, exploration of identity as well as failure of their dream. In general, their poetry articulates bifurcated subjectivity, belonging to neither-here-nor-there, analogically bearing trishanku psyche in the context of the globalized world.